Chromosome-level genome assembly of Phortica okadai, a vector of Thelazia callipaeda - Lingjun Wang; Hongsong Yu; Bo Luo; Rong Yan; Juan Zhou; Hui Liu; Ze Zhang; Wei Sun (Scientific Data)
Abstract Phortica okadai, known as the vector of Thelazia callipaeda in Asia, is of concern to public health in the past few decades. We generated a high-quality chromosome-level genome assembly of P. okadai with a size of 263.82 Mb and a contig N50 of 15 Mb, scaffold N50 of 47.45 Mb, combining PacBio HiFi, Illumina short-reads, and Hi-C sequencing data. Approximately 98.5% of 100 contigs could be properly ordered and oriented into 6 pseudo-chromosomes and a total of 15,052 protein-coding genes were obtained from the P. okadai genome, of which 91.76% were functionally annotated. BUSCO analysis revealed that 96.20% of 1315 predicted genes were clearly covered the conserved invertebrate genes within the database. Additionally, 302 rRNAs, 377 tRNAs, 52 miRNAs, 40 snRNAs and 21 snoRNAs were detected. In conclusion, this high-quality chromosome level reference genome will be a valuable resource for furthering the fields of ecology, genetics, evolution and functional genomics of P. okadai.